科技與人文統整觀點：數位學習與敘事探索─以青少年心理學課程為例 - 劉玉玲Yu-Ling Liu (Higher Education Foundation, 2009)
本文試圖統整人文與科技觀點，運用數位教學平臺與數位教材作為學習資源，在研究者所教授的青少年心理學課程中，利用此平臺作為師資生學習相關議題的學習環境。研究者分析國內、外相關研究建置了內含動態輔導教學案例、靜態教學資源、交流園地，以及知識庫，透過行動和觀察，察覺相關問題，然後反思研擬修改解決問題的循環歷程，調整知識庫的內容，使知識庫的配置更符合教師的學習需求。 研究的第二個重點是運用敘事探究，運用在實踐取向的統整課程上。研究者要求師資生呈現青春生命史，藉由敘說自己的故事或聆聽他人的故事，反省自己的故事或理解別人的故事，在閱讀敘事文本時，能在參與中產生一種認知的功能，特別是當敘說者與這種敘說脈絡、交互作用後，塑造經驗的意義。研究結果發現： 一、數位教學與敘事探究的結合，可以搭起青少年心理學理論與實務連結的橋。 二、數位教學與敘事探究的結合可以達成有效的學習。 三、數位教學與敘事探究可以提升師生的自我覺察與反思的能力。 四、數位教學與敘事探究的結合下，師資生可以形成有意義的學習。 The major purpose of this study is to integrated humanity and science concepts, construct fraction unit of the knowledge web of Adolescent Psychology to assist the professional development of student teachers to bridge the theory-practice gap. The second purpose is through narrative inquiry to look into student teacher inner world from their adolescent experience, enabling them to explore unexamined parts of their personal and professional knowledge of teaching and link them in explicit ways. Finally, the complicated meaning of reflection get played out in the aesthetic ways. The result showed that 1. The E-learning and Narrative Inquiry can aid implement the program, assist student teacher to build theory and practicing experiences. 2. The E-learning and Narrative Inquiry can assist individual to seek oneself inwards. 3. The application of E-learning and Narrative Inquiry can stimulate individual's perception as well as feeling, is a fantastic method and tool in counseling strategy through art therapy. 4. Through E-learning and Narrative Inquiry, individual is able to illustrate their life story with innovate style by using photo, music, pictures.